2017
DOI: 10.1111/jocn.13995
|View full text |Cite
|
Sign up to set email alerts
|

Falls, a fear of falling and related factors in older adults with complex chronic disease

Abstract: The findings from this study provide evidence for the development of nursing interventions for older adults. We recommend early screening for a fear of falling and nursing interventions to decrease the fear of falling through enhancing physical activity level and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
(76 reference statements)
4
16
1
5
Order By: Relevance
“…Other studies have suggested that fear of falling can occur in subjects without a history of falls and no association between previous falls and fear of falling, as detailed later. [52][53][54][55][56][57] Lee et al 54 investigated fear of falling-related factors in 108 older adults with complex chronic disease, and reported that the number of comorbidities, level of physical activity, activity of daily living, and mobility were associated with fear of falling in the regression model, but a history of falling was not associated with fear of falling. Liu 55 investigated the prevalence of fear of falling in 445 robust community-dwelling older people, and reported that 65% of subjects with fear of falling had no history of falls.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that fear of falling can occur in subjects without a history of falls and no association between previous falls and fear of falling, as detailed later. [52][53][54][55][56][57] Lee et al 54 investigated fear of falling-related factors in 108 older adults with complex chronic disease, and reported that the number of comorbidities, level of physical activity, activity of daily living, and mobility were associated with fear of falling in the regression model, but a history of falling was not associated with fear of falling. Liu 55 investigated the prevalence of fear of falling in 445 robust community-dwelling older people, and reported that 65% of subjects with fear of falling had no history of falls.…”
Section: Discussionmentioning
confidence: 99%
“…In this recent study, Lee and colleagues studied factors associated to falls and its relation to fear of falling 1. A total of 108 patients were recruited in a tertiary hospital in Seoul, Korea.…”
Section: Methodsmentioning
confidence: 99%
“…Одними из серьезных осложнений фармакотерапии у пожилых людей являются лекарственно-индуцированные падения, которые служат наиболее распространенной причиной травм, инвалидизации и смертности среди пациентов старше 65 лет [1,6]. Эта проблема особенно актуальна для пациентов экономически развитых стран, в которых возрастает доля людей старшего возраста, вынужденных принимать различные ЛС [7].…”
Section: клинико-фармакологические подходы к прогнозированию риска паunclassified
“…По данным зарубежных авторов, по крайней мере треть людей в возрасте старше 65 лет отмечали, как минимум, одно падение в течение года, а в возрасте старше 75 лет падения наблюдались в 60% случаев [6,[8][9][10]. Паде ния могут быть причиной травм, переломов, ран, повреждений головного мозга и даже смерти.…”
Section: клинико-фармакологические подходы к прогнозированию риска паunclassified